Exploring the Appropriate Price of Semaglutide for Type 2 Diabetes Patients Based on Cost-Utility Analysis in China - Hu, Shanshan; Su, Xiaorong; Deng, Xun; Wang, Yong (Frontiers in Pharmacology, 2021)
Introduction Once-weekly (OW) semaglutide is the first and only oral version of a glucagon-like peptide-1 (GLP-1) analogue approved by the FDA for the treatment of type 2 diabetes (T2D). This research was designed to explore the appropriate price of semaglutide for T2D patients in China based on cost-utility analysis. Methods The baseline patient cohorts of OW semaglutide and once-daily (OD) empagliflozin were sourced from a patient-level meta-analysis integrating the SUSTAIN 2, SUSTAIN 3, SUSTAIN 8 and PIONEER 2 trials. The long-term health and economic outcomes were simulated using the United Kingdom Prospective Diabetes Study Outcome Model 2 (UKPDS OM2) from the Chinese healthcare provider’s perspective. The appropriate price of semaglutide was explored by binary search. One-way sensitivity analysis (one-way SA), probabilistic sensitivity analysis (PSA) and scenario analysis were applied to solve the uncertainty. Results Under the assumption that the annual cost of semaglutide is equal to that of OD empagliflozin, OW semaglutide was superior to OD empagliflozin due to its higher quality adjusted life years (QALYs) and lower total costs. After binary search, the incremental cost-utility ratio (ICUR) of OW semaglutide versus OD empagliflozin was approximately equal to 3λwith an annual cost of semaglutide of $1007.18 and approximately equal toλwith an annual cost of semaglutide of $708.11. Subsequently, the ICUR of OW semaglutide versus OD empagliflozin was approximately 3λandλ, with annual costs of semaglutide of $877.43 and $667.04, respectively, adjusted by one-way SA. Utimately, the cost-utility results with annual costs of semaglutide of $877.43 and $667.04 were robust to PSA and scenario analysis. Conclusion In conclusion, the annual cost of semaglutide appears to be appropriate between $667.04 and $877.43 for T2D patients in China.